Kisah Luth (Lot) dan Kejahatan Kaum Sodom: Suatu Perbandingan Lintas Tekstual dalam Al-Qur'an dan Alkitab - Andreas Kristianto; Daniel K Listijabudi (Theologia in Loco, 2021)
The story of Luth (read: Lot) is usually read as a text about homosexuality in both Christianity and Islam. By exploring a cross-textual reading from leading Muslim interpreters in Indonesia, Hamka with Al Azhar Juzu Commentary, Quraish Shihab with Al Misbah Commentary and interpretation of the Ministry of Religion, this article unveils the hidden meaning of Luth’s story, which today’s readers often overlook, especially concerning the text of the Qur’an, namely Surah Asy-Syu’ara 26: 166-175, Surah Al-Naml 27: 54-59 and Surah Al-Ankabut 29: 28-30. Through a cross-textual reading, the article unveils the new meaning of the story, i.e., the crimes of the Sodomites not only related to sexual violence and hostility, but also, with the terms al-fahisyah (abomination), al-sayyiat (crime), al-musrifun (people who are excessive), al-’adun (people who transgress), al-jahl (ignorance), and alkhaba’is (bad deeds), which are the accumulation of various kinds of crimes, crimes, and abominations degrading humanity. The cross-textual reading between the interpreters of the Qur’an and the Bible provides the viewpoints, insights, and values in the cross-textual hermeneutical encounter of different religions, traditions, and scriptures.